2017
DOI: 10.1080/10810730.2016.1252816
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing Foreshadowed Death Narratives: Examining the Impact of Character Death on Narrative Processing and Skin Self-Exam Intentions

Abstract: Narratives are common in health campaigns and interventions, with many depicting individuals battling a particular illness or disease. Past research has focused primarily on the form and effects of survivor stories, but considerably less attention has been devoted to stories in which 1 or more of the central characters passes away. The goal of the current study was to compare the relative persuasive impact of survivor and death narratives in influencing skin prevention behaviors and to test narrative mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 52 publications
2
10
1
1
Order By: Relevance
“…Bivariate analyses showed null effects and SEM results showed a small but significant negative association between information plus a narrative vs. information only with CRCS intentions, which fail to support Hypothesis 1. This is not the first narrative study with unexpected findings (e.g., Jensen et al, 2017;Nyhan, Reifler, Richey, & Freed, 2014). Consistent with prior reviews, we found small effect sizes, which may have limited the statistical differences found with our sample.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Bivariate analyses showed null effects and SEM results showed a small but significant negative association between information plus a narrative vs. information only with CRCS intentions, which fail to support Hypothesis 1. This is not the first narrative study with unexpected findings (e.g., Jensen et al, 2017;Nyhan, Reifler, Richey, & Freed, 2014). Consistent with prior reviews, we found small effect sizes, which may have limited the statistical differences found with our sample.…”
Section: Discussionsupporting
confidence: 86%
“…To contribute to the growing literature on the message processing and persuasion effects of narratives, we sought to complement previous studies testing path models (Jensen et al, 2014;Jensen, Yale, Krakow, John, & King, 2017;Krakow et al, 2017;McQueen et al, 2011;Moyer-Guse & Nabi, 2010;Murphy et al, 2011;Quintero Johnson et al, 2013). We expected to find support for the inter-correlations between model variables and indirect effects on intention and behavior in our conceptual model.…”
Section: Objectivementioning
confidence: 99%
“…Los mensajes construidos en clave narrativa se utilizan cada vez más en la comunicación sanitaria para alcanzar objetivos de salud pública, como la prevención y detección de enfermedades (Frank, Murphy, Chatterjee, Moran y Baezconde-Garbanati, 2015;Green, 2006;Jensen, Yale, Krakow, John y King, 2017;Thompson y Kreuter, 2014). Se ha observado que los mensajes narrativos de salud son capaces de provocar cambios de creencias y actitudes coherentes, así como estimular comportamientos saludables (De Graaf, Sanders y Hoeken, 2016).…”
Section: Mensajes Narrativos De Prevención Del Tabaquismounclassified
“…nonexpert audiences about science. A number of recent journal articles have explored the impact of narratives across a range of science communication contexts (Cooper & Nisbet, 2016;Jensen, Yale, Krakow, John, & King, 2017;Muurlink & McAllister, 2015;Shaffer et al, 2017) and the National Academy of Sciences devoted a recent workshop to explore how narratives can benefit science (National Academies of Sciences, Engineering, & Medicine, 2017). This interest extends outside of academic contexts.…”
mentioning
confidence: 99%